Antibodies to hepatitis C virus major antigens associated with certain stages of hepatitis C virus infection - Cavinta, Lolita L. (1998)
This study was done to determine the presenceof antibodies to major hepatitis C virus antigens at certain stages of HCV infection and disease in symptomatic, jaundiced patients and in asymptomatic inmates from Muntinlupa, Bilibid prison.Serum samples from fourteen symptomatic patients from San Lazaro and twenty five asymptomatic inmates from the National Penitentiary, Muntinlupa, who were found to be positive for anti-Hepatitis C virus antibodies by enzyme immunoassay (HCV-EIA) were studied using an HCV recombinant immunoblot assay (RIBA 3.0, Ortho-Diagnostics, U.S.A.) that determines specific antibodies to 4 antigenic components, 3 of which are nonstructural (c100, c33, NS5) and 1 structural (c22) antigens.Seven out of 15 (50) symptomatic patients were RIBA positive and recognized 3-4 antigens. The remaining 50were RIBA indeterminates, recognizing only one antigen. None was RIBA negative. On the other hand, 22 out of 25 (88) asymptomatic subjects were RIBA positive with 72recognizing 3-4 antigens and 18recognizing 2 antigens. A low 12were indeterminates. None of the asymptomatic subjects was also negative for RIBA. When antibodies to HCV were analyzed separately, anti-c33 was the most frequently found antibody in both the symptomatic patients (86) and the asymptomatic subjects (88).Co-infection with hepatitis B virus (HBV) was also found among symptomatic patients (5/14, 36) and asymptomatic subjects (2/15, 8). 80of the symptomatic patients with concurrent HBV infection were RIBA positive in contrast to the 33RIBA positivity among symptomatic patients with pure HCV infection. For the asymptomatic subjects, the 2 who had concurrent HBV infection were both RIBA positive.A limited seroconversion data suggest that approximately 6-13 weeks or less maybe needed for a patient to resolve his HCV infection, otherwise, development of chronicity might follow.The level of alanine aminotransferase (ALT) among symptomatic patients was higher in RIBA 3.0 positive symptomatic patients than in RIBA 3.0 positive asymptomatic subjects. The concentration of antibodies to the different HCV antigens expressed by the s/c ratio by EIA was not predictive of the results of RIBA whether ALT was low, intermediate or high. In conclusion, even from a limited number of samples tested, there are indeed differences in the HCV antibody profile between symptomatic patients and asymptomatic subjects. This difference may have a diagnostic value. It is therefore, recommended that a larger number of samples be tested to confim the results of this study.
Thesis (Master of Science in Public Health, Medical Microbiology)--University of the Philippines Manila.
Keywords: Hepatitis C